Microbiomes of North American Triatominae: The Grounds for Chagas Disease Epidemiology - Rodríguez-Ruano, Sonia M.; Škochová, Veronika; Rego, Ryan O. M.; Schmidt, Justin O.; Roachell, Walter; Hypša, Václav; Nováková, Eva (Frontiers in Microbiology, 2018)
Insect microbiomes influence many fundamental host traits, including functions of practical significance such as their capacity as vectors to transmit parasites and pathogens. The knowledge on the diversity and development of the gut microbiomes in various blood feeding insects is thus crucial not only for theoretical purposes, but also for the development of better disease control strategies. In Triatominae (Heteroptera: Reduviidae), the blood feeding vectors of Chagas disease in South America and parts of North America, the investigation of the microbiomes is in its infancy. The few studies done on microbiomes of South American Triatominae species indicate a relatively low taxonomic diversity and a high host specificity. We designed a comparative survey to serve several purposes: I) to obtain a better insight into the overall microbiome diversity in different species, II) to check the long term stability of the interspecific differences, III) to describe the ontogenetic changes of the microbiome, and IV) to determine the potential correlation between microbiome composition and presence in the vector gut of Trypanosoma cruzi, the causative agent of Chagas disease. Using 16S amplicons of two abundant species from the southern US, and four laboratory reared colonies, we showed that the microbiome composition is determined by host species, rather than locality or environment. The OTUs (Operational Taxonomic Units) determination confirms a low microbiome diversity, with 12-17 main OTUs detected in wild populations of T. sanguisuga and T. protracta. Among the dominant bacterial taxa are Acinetobacter and Proteiniphilum but also the symbiotic bacterium Arsenophonus triatominarum, previously believed to only live intracellularly. The possibility of ontogenic microbiome changes was evaluated in all six developmental stages and faeces of the laboratory reared model Rhodnius prolixus. We detected considerable changes along the host’s ontogeny, including clear trends in the abundance variation of the three dominant bacteria, namely Enterococcus, Acinetobacter and Arsenophonus. Finally, we screened the samples for the presence of Trypanosoma cruzi. Comparing the parasite presence with the microbiome composition, we assessed the possible significance of the latter in the epidemiology of the disease. Particularly, we found a trend towards more diverse microbiomes in Trypanosoma cruzi positive T. protracta specimens.